Educational Technology Evolvement During The Covid-19 Pandemic - Hamim Hamdani; Ermaya Suradinata; Layla Kurniawati; Wangsih Wangsih (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The COVID-19 pandemic has become a global problem that has impacts on various government sectors. The education sector included the fields of science and technology, is one of the main pillars that must be maintained and improved under any circumstances. This study was conducted to determine the evolvement of educational technology during the COVID-19 pandemic. Articles related to educational technology have been collected through data-based Mendeley, using the keyword "Education Technology". The articles were filtered through several stages, as follows; a number of 163,616 articles were screened by related title, which then 33,228 articles were obtained after bering filtered by year 2020-2022. Then 23,747 articles were identified after being filtered to document type, journal (Education and Information technologies) obtained 197 articles, which then filtered by access type (open access) acquired 84 articles, and eventually 20 articles were eligible by inclusion and exclusion criteria that focused on the topic of educational technology during the COVID-19 pandemic. The findings of the article analysis were: 1) Educational technology during the COVID-19 pandemic, 2) Types of educational technology, and 3) Factors that influence the application of educational technology, and 4) Impact of educational technology. Educational technology is significantly important for continuity of learning process during the COVID-19 pandemic.